Exploring Moth Diversity in the Ecosystem of Mangalore University Campus, Karnataka - Yambem Tenjing Singh; Tharavathy, N.C; L. Bina Chanu (International Journal of Insects, 2024)
The moth is one of the genera of insects of the order Lepidoptera, where butterflies share the same genus. They have nocturnal habits and a high attraction to light. Moths have various sizes, shapes, and colors, with many having duller colors. A study was conducted on the diversity of moth species in Mangalore University campus, Mangalore, Karnataka, for eight months (August 2006 to March 2007). We recorded 39 moths belonging to 7 families and 24 genera. This study shows that Erebidae (30.8%) was the most dominant family according to the total number of individuals, followed by Sphingidae (28.2%) and Noctuidae (12.8%). Saturniidae and Geometridae represent 10.3% each, followed by Eupterotidae (5.1%) and Uraniidae (2.6%). Only one unidentified species from each family, Geometridae and Noctuidae, was discovered. Based on wingspan, Plecoptera sp. (family Erebidae) was the tiniest moth, while Attacus atlas (family Saturniidae) was the largest. We updated the scientific and family names of moth species with the help of the Global Biodiversity Information Facility (GBIF) database. The Hostel Old Block had the most extensive documented diversity of moth species in our study. On the other hand, the Survana Hostel had the fewest species of moths recorded. In the environment, moths act as excellent pollinators and, at the same time, serve as good food items for other animals. The present study reveals that the forest provides suitable environmental conditions for moths. We suggest further research to explore different aspects of lepidopteran ecology, like behaviour, population dynamics, and responses to environmental changes in the university campus.
Keywords: Diversity; GBIF; Lepidoptera; Mangalore; Moths